Acceleration of Land Certification with Unmanned Aerial Vehicle in Toll Road Construction Area - Bambang Edhi Leksono; Agoes Soewandito Soedomo; Levana Apriani; Nanin Trianawati Sugito; Atifah Rabbani (Faculty of Geography, Universitas Gadjah Mada, 2019)
Toll roads is one important component to improve the progress of a country, because with the addition of toll roads, the accessibility easier and can advance the economic movement. One of the toll road construction that is underway is construction of Cileunyi - Sumedang - Dawuan (Cisumdawu). The Cisumdawu Toll is prepared to tackle congestion on Jalan Cadas Pangeran and facilitate access to Kertajati International Airport. The construction of the Cisumdawu toll road itself is inseparable from land acquisition problems. Land acquisition is a process to purchase community-owned land which passed by toll road. Land acquisition requires a land certificate to facilitate legal affairs, unfortunately many land in rural areas do not yet have a certificate. This certification process can be assisted by unmanned aerial vehicle (UAV) technology to map parcel data. This research examines how UAV assist in the acceleration of certification for land parcels to be acquired.